Social and Environmental Challenges caused by Legacy Gold Mining in Johannesburg: Government’s Action Plan - Sunday Mishack Mabaso (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
This chapter examines, through a literature review, the social and environmental challenges experienced by communities living around legacy mine sites (shafts and dumps), past and present legislative framework that resulted in these legacy mine sites and how communities find themselves living next to these mine sites in Johannesburg, which results in these problems. The paper further explores the government’s, particularly the DMRE, proposed initiatives to empower those who intend to extract value from these abandoned mines while curbing the scourge of crime in affected communities. The creation of employment opportunities for the youth, in particular, will go far in the eradication of illegal mining. This intervention through effective legislation must be paired with improved implementation and enforcement of the legislation. Even in locations where gold mining halted more than 100 years ago, legacy mine shafts and garbage dumps in the Witwatersrand continue to provide social and environmental problems for communities. Conflict arises between the communities and authorities due to the sluggish removal of these gold mine shafts and waste dumps (or lack thereof), particularly the Department of Mineral Resources and Energy (DMRE), which is the relevant authority in the area of environmental management in mining.